CRM (Customer Relationship Management) Effect on Increasing Customer Loyalty (Case Study: Bank X – Pasuruan Branch Officer) - Taufik Rachmad Fauzy; Dwi Mei Riya Ristanti (Tibuana, 2023)
This study analyzes the influence of Customer Relationship Management (CRM) Customer Loyalty on the State Savings Bank in Pasuruan. CRM is explained by identifying indicators, differentiation, interaction and customization. At the same time, the indicators are explained by loyalty, satisfaction, emotional ties, trust, behaviour, and history with the company. The analysis results show the effect of increasing CRM on the absolute loyalty of the State Savings Bank in Pasuruan. CRM influences 92.3%, and other factors outside the model influence 7.7%. The most influential factor interaction on height was 73%, followed by identification at 71.1%, Costumize factor at 61.58% and differentiation factor at 51.8%. The conclusion is that CRM, which is explained by these four factors, greatly influences fostering and increasing customer loyalty. Customers need special attention from bank management in making transactions to meet their needs and other services that can be accessed quickly and easily.